Pemanfaatan Media Teknologi Informasi Terhadap Minat Belajar Mahasiswa Bimbingan dan Konseling Islam : Utilization of Information Technology Media on Islamic Guidance and Counseling Students' Interest in Learning - Dilla Astarini; Yuliana Yuliana; Penti Novita Sari; Mulia Syarianti (UIN Kiai Haji Achmad Siddiq Jember, 2023)
This article aims to determine the use of information technology on students' interest in learning at UIN Fatmawati Sukarno Bengkulu. This research is a quantitative research, with a population of 250 students active in Islamic guidance and counseling. The sample in this research was 52 students. The sampling technique in this research is the cluster random sampling technique. The research instrument used an information technology and learning interest questionnaire. With data analysis techniques using linear regression. The research results showed that R was .278a >0.05. This means that the hypothesis is accepted, there is a positive use of information technology on interest in learning, with an influence value of .078 (7.8%). This means that 7.8% of information technology influences a person's interest in learning and 92.2% is influenced by other variables.